Bending mechanism for piezoelectric transducer - Mohd Asry, Anis Maisarah; Mustafa, Farahiyah; Ahmad, Aznizam; Sim, Sy Yi; Sahari, Norain (WARSE, 2020)
This paper tests and analyzes a piezoelectric transducer with bending mechanism based on the bending condition of piezoelectric transducer after applying a force on the bending mechanism that increase the stress on the piezoelectric surface and thus increase the electrical charges produced An impact force is being exerted onto bending mechanism to bend the piezoelectric transducer and hence generating useable electrical power. The proposed prototype bending mechanism was built by using SolidWork soft-ware and manufactured by employing 3D printer technology to conduct the evaluation. This bending mechanism is divided into two parts, presser and support housing. The presser is design with four different diameter to test the piezoelectric transducer. A round piezoelectric transducer with the size of 50 mm in diameter is used to demonstrate the experiment. This piezoelectric transducer is placed in support housing and the presser is used to give pressure to the piezoelectric transducer. A subject is assigned to hold the presser and press in on the surface of the piezoelectric transducer. It can be seen from the experiment that the last presser with diameter 22.35 mm generated the highest output voltage about 44.0 V. The reported mechanism is a promising candidate in the application of energy harvesting by using piezoelectric transducer for powering various low power output devices.